2003
DOI: 10.1016/s0168-6496(03)00200-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial indicators of aquatic ecosystem change: current applications to eutrophication studies

Abstract: Human encroachment on aquatic ecosystems is increasing at an unprecedented rate. The impacts of human pollution and habitat alteration are most evident and of greatest concern at the microbial level, where a bulk of production and nutrient cycling takes place. Aquatic ecosystems are additionally affected by natural perturbations, including droughts, storms, and floods, the frequency and extent of which may be increasing. Distinguishing and integrating the impacts of natural and human stressors is essential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(126 citation statements)
references
References 34 publications
2
120
0
4
Order By: Relevance
“…Bacteria in surface sediment have massive diversity and rapid growth rate, and their populations are largely influenced by pollutants of water columns [7,8]. Recently, molecular method-based studies have indicated that bacterial diversity in sediment has been linked with impacts of anthropogenic activities, such as increase of eutrophication and chemical pollution [9][10][11][12][13], changes in species of phytoplankton or zooplankton [14][15][16], and operating a dredging, reclamation, or remediation project [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria in surface sediment have massive diversity and rapid growth rate, and their populations are largely influenced by pollutants of water columns [7,8]. Recently, molecular method-based studies have indicated that bacterial diversity in sediment has been linked with impacts of anthropogenic activities, such as increase of eutrophication and chemical pollution [9][10][11][12][13], changes in species of phytoplankton or zooplankton [14][15][16], and operating a dredging, reclamation, or remediation project [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 70% of the world's population and 85% of the Australian population is concentrated within 50 km of the coast (Paerl et al 2003. Many areas of the Australian coastline have been extensively modified and in some cases heavily degraded over a relatively short period of time since European settlement began over 200 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia/ anoxia may lead to the replacement of aerobic species with microaerophilic and anaerobic species and as a result alter ecosystem functions such as nutrient cycling (Paerl 1998). Overall, microbial activity in marine sediments is determined by geographic position, sedimentation rate, quality of the sedimenting material, temperature and sediment chemical conditions, but it is well established that sediment communities respond rapidly to altered nutrient input (Battersby & Brown 1982, Paerl 1998, Cloern 2001, Paerl et al 2003.…”
Section: Introductionmentioning
confidence: 99%